Vitreous inorganic coating agent for maintenance-free stone tiles and method for producing maintenance-free stone tiles

A moisture-curing vitreous inorganic coating agent with controlled catalyst and silica ratios stabilizes curing and adhesion across humidity variations, addressing maintenance issues in stone surfaces by providing a durable, high-gloss finish.

JP7612958B2Active Publication Date: 2025-01-15KYUSHU HI TECH
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021081976
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-23
Publication Date
2025-01-15
Estimated Expiration
2041-03-23

AI Technical Summary

Technical Problem

Existing maintenance methods for stone surfaces, such as marble and granite, face issues with curing stability under varying humidity conditions, adhesion problems leading to peeling and cracking, and the need for frequent polishing to maintain gloss and hardness.

Method used

A moisture-curing vitreous inorganic coating agent using a specific composition of polyorganosiloxane, silane coupling agent, ultrafine colloidal silica, and a phosphoric acid catalyst, with controlled ratios to stabilize curing across a wide range of humidity conditions, ensuring high adhesion and hardness without cracking or peeling.

Benefits of technology

The coating achieves stable curing and high adhesion, allowing for immediate post-polishing without peeling, maintaining a high-gloss finish equivalent to polished stone, with improved abrasion resistance and durability under varying humidity levels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612958000010
    Figure 0007612958000010
  • Figure 0007612958000001
    Figure 0007612958000001
  • Figure 0007612958000002
    Figure 0007612958000002
Patent Text Reader

Abstract

To provide a glassy inorganic coating agent for a maintenance-free stone tile in which the hardened state is stable even under wide humidity conditions of low humidity (65% or less), good humidity (65-75%) and high humidity (75% or more), and to provide a method for producing the tile.SOLUTION: A glassy inorganic coating agent for a maintenance-free stone tile contains a polyorganosiloxane consisting of a mixture of alkoxysilanes with at least one or more alkoxysilanes having four and three functional groups, and a silane coupling agent having an epoxy functional group. 30-60 wt.% of the polyorganosiloxane, 5-20 wt.% of the silane coupling agent, 20-40 wt.% of the ultrafine colloidal silica, and more than 5 wt.% and 10 wt.% or less of a phosphate-based catalyst as a catalyst to enhance the reaction hardenability are added to the 100 weight ratio of the main component containing ultrafine colloidal silica with an average particle size of 5-60 nm.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a moisture-curing coating that forms a vitreous inorganic coating layer with excellent hardness and specular gloss on the surface of various stone materials such as marble and granite, and relates to a vitreous inorganic coating agent for maintenance-free stone tiles that remains in a stable cured state under a wide range of humidity conditions, including low humidity conditions (65% or less), comfortable humidity conditions (65-75%), and high humidity conditions (75% or more), and a method for producing maintenance-free stone tiles. [Background technology]

[0002] Traditionally, the maintenance of various stone floors such as marble, artificial stone, and terrazzo has generally been done by waxing or polishing with diamond grindstones. With the waxing method, there are many issues with quality and gloss retention, and the wax must be removed periodically. If the wax is not removed, the appearance will be significantly damaged by blackening and dirt, making it difficult to maintain a high-quality condition for a long time. Furthermore, the wax remover itself is strongly alkaline, which can reduce the gloss of the stone or weaken the stone itself, so this method of maintenance is not very recommended. On the other hand, polishing with diamond grindstones requires about five to seven polishing steps to achieve a mirror finish, which is too much work for maintenance, and even if polished, the gloss will fade after a few months because marble is a soft stone. Therefore, unless polishing is done regularly, it is difficult to maintain a high-quality condition for a long time. In addition, the water used in polishing weakens the stone itself, making it a less desirable method for stone. In order to improve these problems, various coating agents for stone have been proposed in recent years, but even if these coating agents are used, the following issues remain:

[0003] (1) Cure stability under high and low humidity conditions; In order to make it possible to polish the coating immediately after application, it is necessary to accelerate the curing property. It is also desirable to have a moisture-curing coating agent that maintains a stable cured state under a wide range of humidity conditions, including low humidity conditions (65% or less), comfortable humidity conditions (65-75%), and high humidity conditions (75% or more).

[0004] (2) No cracks occur even when cured for a short time; In order to form a coating film with good drying and curing properties, a phosphoric acid catalyst is used, and the phosphoric acid catalyst must cure the coating film in a short time. However, in order to cure in a short time, it is necessary to suppress the occurrence of cracks, so it is desirable to suppress extreme curing by blending colloidal silica with a water solvent, and at the same time, to contribute to the curing promotion of polyorganosiloxane and silane coupling agent with epoxy functional groups, so that cracks do not occur even when curing in a short time.

[0005] (3) Unstable adhesion; Marble, artificial stone, terrazzo, etc., which are mainly composed of calcium carbonate, basically have poor adhesion to hard coating agents, and after application, vertical scratches and peeling may occur due to poor adhesion. In addition, shrinkage caused by condensation reaction makes the coating film prone to cracks and peeling, significantly impairing the quality.

[0006] Due to the above-mentioned problems, currently, both in Japan and overseas, the maintenance of various stone materials in various commercial facilities, hotels, public facilities, amusement facilities, etc. is generally performed by polishing or waxing, and no maintenance-free stone tiles are available.

[0007] Previously, the applicant provided a maintenance-free stone tile and a coating agent therefor, as well as a manufacturing method for such a tile, in Patent Document 1 (JP Patent Publication No. 2016-210670). In Patent Document 1, it is described that "a main component 100 weight ratio containing polyorganosiloxane consisting of a mixture of at least one or more alkoxysilanes having tetrafunctional and trifunctional alkoxysilanes, a silane coupling agent having an epoxy functional group, and ultrafine colloidal silica having an average particle size of 5 to 20 nm is used, and the main component 100 weight ratio contains 30 to 50 wt% of polyorganosiloxane, 5 to 20 wt% of silane coupling agent, 20 to 40 wt% of ultrafine colloidal silica, and phosphoric acid or the like as a catalyst for enhancing reaction curing property. The patent disclosed that the present invention provides a maintenance-free vitreous inorganic coating agent for stone tiles, which is made by adding 0.1 to 5.0 wt% by weight of either a catalyst selected from the group consisting of a titanium-based catalyst and an aluminum-based catalyst, or 0.1 to 20.0 wt% by weight of a catalyst selected from the group consisting of a titanium-based catalyst and an aluminum-based catalyst, and which has a coating layer with a gloss of 80 or more and a coating layer with a pencil hardness of 12H or more on the surface, and which has good water resistance, stain resistance, slipperiness and adhesion and is crack-free. The patent also discloses that the present invention provides a maintenance-free vitreous inorganic coating agent for stone tiles, which is made by adding 0.1 to 5.0 wt% by weight of either a catalyst selected from the group consisting of a titanium-based catalyst and an aluminum-based catalyst, or 0.1 to 20.0 wt% by weight of a catalyst selected from the group consisting of a titanium-based catalyst and an aluminum-based catalyst, and which has a gloss of 80 or more and a coating layer with a crack-free coating layer with a pencil hardness of 12H or more on the surface.

[0008] However, in the above Patent Document 1, it is described that a titanium-based catalyst and / or an aluminum-based catalyst can also be used, and that phosphoric acid or the like is added as a catalyst at a weight ratio of 0.1 to 5.0 wt%, and the phosphoric acid-based catalyst is not added in a range of more than 5 wt% and less than 10 wt% as in the present invention, and there is no description that, of the 20 to 40 wt% of the ultrafine colloidal silica, 5 wt% to 15 wt% of the water-solvent colloidal silica is added based on the total amount. Therefore, even if a stable curing state can be obtained under comfortable humidity conditions (65 to 75%), a stable curing state cannot be obtained under a wide range of humidity conditions, including low humidity conditions (65% or less) and high humidity conditions (humidity 75% or more). Problems to be solved by the invention

[0009] In order to solve the above problems, the present invention aims to provide a maintenance-free vitreous inorganic coating agent for stone tiles that stably accelerates hardening under a wide range of humidity conditions, including low humidity (65% or less), comfortable humidity (65 to 75%), and high humidity (75% or more), and a method for manufacturing such tiles.

[0010] The invention of claim 1 provides a maintenance-free vitreous inorganic coating agent for stone tiles, which comprises a polyorganosiloxane, at least one or more of which is a mixture of alkoxysilanes having tetrafunctional and trifunctional groups, and a silane coupling agent having an epoxy functional group, and which contains ultrafine colloidal silica having an average particle size of 5 to 60 nm, in a weight ratio of 100% of a main component, the main component being 30 to 60 wt% of the polyorganosiloxane, 5 to 20 wt% of the silane coupling agent, and 20 to 40 wt% of the ultrafine colloidal silica, and in order to enhance reaction curing, a phosphoric acid catalyst is added in a weight ratio of more than 5 wt% and not more than 10 wt% without using a titanium-based catalyst and / or an aluminum-based catalyst, and among the 20 to 40 wt% of the ultrafine colloidal silica, 5 wt% to 15 wt% of colloidal silica in water solvent is added relative to the total amount of the fine colloidal silica.

[0011] In this invention, in order to be able to polish immediately after applying the maintenance-free type inorganic glass coating agent for stone tiles, it is necessary to promote the hardening. Therefore, titanium-based catalysts and aluminum-based catalysts are not suitable as catalysts. However, since phosphoric acid-based catalysts are sensitive to the temperature and humidity conditions during application, it was considered difficult to use the sol-gel method, but the amount of acid-based catalyst and the amount of water were adjusted as parameters. That is, the amount of acid-based catalyst was added in a range of more than 5 wt% and less than 10 wt% under high and low humidity conditions. In addition, among 20 to 40 wt% of ultrafine colloidal silica, 5 wt% to 15 wt% of water-solvent colloidal silica was added to the total amount of the ultrafine colloidal silica to promote hydrolysis, and the hardening property was stabilized under high and low humidity conditions by balancing the amount of water and the amount of phosphorus catalyst. Under each condition, the phosphoric acid catalyst is more than 5wt% and 10wt% and the ultrafine colloidal silica is 20-40wt%, and the water-solvent colloidal silica is added at 5wt%-15wt% based on the total amount of the ultrafine colloidal silica, so that the hardening is stable and the polishing after hardening is also stable. This makes it possible to obtain a maintenance-free glassy inorganic coating agent for stone tiles in which the hardening state is stable under a wide range of humidity conditions, including low humidity conditions (65% or less), comfortable humidity conditions (60-75%), and high humidity conditions (75% or more). In other words, the stable hardening property specifically means that the coating has the same hardness under all conditions under low humidity, comfortable humidity, and high humidity conditions, and can be polished afterwards without peeling off.

[0012] The invention of claim 2 is a composition comprising a polyorganosiloxane, at least one or more of alkoxysilanes being a mixture of alkoxysilanes having tetrafunctional and trifunctional groups, and a silane coupling agent having an epoxy functional group, and a superfine colloidal silica having an average particle size of 5 to 60 nm, in a weight ratio of 100 of a main component, the polyorganosiloxane being 30 to 60 wt%, the silane coupling agent being 5 to 20 wt%, the superfine colloidal silica being 20 to 40 wt%, and a phosphoric acid catalyst being added in a weight ratio of more than 5 wt% but not more than 10 wt%, without using a titanium-based catalyst and / or an aluminum-based catalyst, as a catalyst for enhancing reaction curing, and the superfine colloidal silica being 20 to 40 wt%, the water-solvent The method for producing maintenance-free stone tiles includes the steps of: adjusting a viscosity of a glassy inorganic coating agent for maintenance-free stone tiles, in which colloidal silica is added in an amount of 5 wt% to 15 wt% based on the total amount of the ultrafine colloidal silica, to 3 cSt to 6 cSt (mm2 / s), and coating the agent on a stone floor surface whose stone surface has been roughened in advance by diamond polishing; curing the agent at room temperature one hour to one day after the coating process so that the pencil hardness is equivalent to a pencil hardness of 12H or more when measured based on correlation data between a pencil hardness test and an abrasion resistance test; and then polishing the surface of the coating layer with a diamond grindstone to obtain a surface roughness of Rmax 0.8s or less and a specular gloss of 80 or more.

[0013] In this invention, in order to be able to polish immediately after applying the maintenance-free type stone tile glassy inorganic coating agent, it is necessary to promote the hardening. Therefore, titanium-based catalysts and aluminum-based catalysts are inappropriate. However, since phosphoric acid-based catalysts are sensitive to the temperature and humidity conditions during application, it was considered difficult to use the sol-gel method, but the amount of phosphoric acid-based catalyst and the amount of water were adjusted as parameters. That is, the amount of phosphoric acid-based catalyst was varied from more than 5 wt% to less than 10 wt% under high and low humidity conditions. In addition, of the 20 to 40 wt% of the ultrafine colloidal silica, 5 wt% to 15 wt% of water-solvent colloidal silica was added to the total amount of the ultrafine colloidal silica. By making a part of the colloidal silica water-solvent, hydrolysis was promoted, and the balance between the amount of water and the amount of phosphoric acid-based catalyst was achieved, stabilizing the hardening under high and low humidity conditions. The test results showed that under each condition, a phosphoric acid catalyst of more than 5 wt% and within 10 wt%, and a water-solvent colloidal silica of 5 wt% to 15 wt% provided stable hardening, and polishing after hardening was also more stable. This provides a coating method for a maintenance-free glassy inorganic coating agent for stone tiles that provides a stable hardened state under a wide range of humidity conditions, including low humidity conditions (65% or less), comfortable humidity conditions (60-75%), and high humidity conditions (75% or more).

[0014] [Patent Document 1] JP 2016-210670 A Examples of the present invention

[0015] In the present invention, the stone material can be used as flooring materials such as marble, granite, artificial stone, terrazzo, ceramic tiles, etc. As the tetrafunctional and trifunctional alkoxysilanes of the present invention, mainly tetramethoxysilane, methyltrimethoxysilane, phenyltrimethoxysilane, tetraethoxysilane, methyltriethoxysilane, phenyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, disyltrimethoxysilane, decyltrimethoxysilane, trifluoropropyltrimethoxysilane, methyl silicate, ethyl silicate, etc. are used.

[0016] Silane coupling agents include epoxy functional silane coupling agents such as β-(3,4 epoxycyclohexyl)ethyltrimethoxysilane, Y - glycidoxypropyltrimethoxysilane, Y - glycidoxypropylmethyldiethoxysilane, Y - Glycidoxypropyltriethoxysilane, etc. is used.

[0017] Colloidal silica used to maintain high hardness is an organic solvent dispersion type tile, such as methanol, ethanol, isopropanol, methyl ethyl ketone, methyl ethyl, methyl isobutyl, etc. Also, water-dispersed colloidal silica is used. In either case, a particle size of 5 nm to 60 nm is used. In addition, of the 20 to 40 wt% ultrafine colloidal silica, 5 wt% to 15 wt% of water-solvent colloidal silica is added to 100 wt% of the colloidal silica. As a catalyst, a titanium-based catalyst and / or an aluminum-based catalyst is not used, and a phosphoric acid-based catalyst is added at a weight ratio of more than 5 wt% to 10 wt%. The phosphoric acid-based catalyst is diluted with alcohol (isopropyl alcohol) and has a solid content of 20 to 30%.

[0018] The physical properties of commonly used marble are shown in Table 1. As shown in these, the water absorption rate of marble is extremely low, at 0.17% or less. [Table 1]

[0019] The properties required for this coating agent are, first, that the cured state is stable under a wide range of humidity conditions, including low humidity conditions (65% or less), comfortable humidity conditions (65-75%), and high humidity conditions (humidity 75% or more), as a moisture-curing coating, and that a hardness equivalent to 12H or more is obtained about 1 hour to 1 day after application. In other words, it has been confirmed that peeling due to polishing does not occur if the hardness is 12H or more, and by making it equivalent to 12H or more, a coating film with high hardness and high adhesion is obtained (if the adhesion is poor, even if it is a high-hardness film, it will show a low pencil hardness value). In addition, if it is equivalent to 12H or more, it is possible to maintain extremely excellent gloss, about 10 to 20 times, compared to the gloss maintenance of marble polishing. In addition, the evaluation of pencil hardness of 11H or more is shown as the equivalent value measured based on the correlation data of the pencil hardness test and the abrasion resistance test shown in Figure 1.

[0020] Secondly, the surface of the coating agent can be polished. After the glassy coating agent has hardened, it is polished with diamond to a surface roughness of Rmax 0.8s or less and a mirror gloss of 80 or more, resulting in a high-quality finish equivalent to that achieved with regular stone polishing. As a result, problems such as "slipperiness" and "adhesion of dirt" can be prevented, and this condition can be maintained for a long period of time. Polishing test with diamond grinding wheel

[0021] Table 2 below shows the gloss value, surface roughness, and finish when the coated surface is polished using the roughness of a diamond grindstone as a parameter. The results show that polishing with a grindstone of #5000 or greater can achieve a specular gloss value of 80 or more with a surface roughness of Rmax 0.8s or less, resulting in a finish with excellent specular gloss similar to that of general ceramic tiles or granite. [Table 2]

[0022] From the above results, by polishing with a grindstone of #5000 or more, a surface roughness of Rmax 0.8s or less and a mirror gloss of 80 or more can be obtained, resulting in a mirror finish that is generally referred to as a mirror surface. Furthermore, if the grit size of the grindstone is increased (for example, to #8000, #10000, etc.), the gloss value and surface roughness will be further improved, but on the other hand, the polishing ability will decrease and it will take time to achieve a mirror finish. Therefore, using a #5000 grindstone will allow you to obtain a good mirror surface condition without spending a lot of processing time. Experimental example

[0023] First, as shown in Table 3 below, under comfortable humidity conditions (65-75%), the polyorganosiloxane was 40wt%, the silane coupling agent was 15wt%, and the phosphoric acid catalyst amount was fixed at 6wt%, and the colloidal silica contained in the whole was varied to 20-40wt%, and the hardness, etc. was confirmed when the water-solvent colloidal silica was varied to 0-40wt% relative to the total amount of the colloidal silica of 100wt%. Then, polishing was performed with a #5000 grindstone to confirm the presence or absence of peeling of the coating layer. The thickness of the coating layer was 20μm. The test was performed on a glass plate with relatively good adhesion, and the evaluation was performed in a state where it was not affected by the adhesion to the substrate.

[0024] [Table 3] [Test Method] *The comfortable humidity conditions for coating were set in the autumn when the weather was fine, with the humidity gauge measuring 65-75%. *The surface of the glass plate was roughened with GC powder #1000 and then coated with a coating agent to a thickness of 20 μm. *JIS K5600 scratch hardness test (pencil method, hereinafter referred to as "pencil hardness test") TIFF0007612958000004.tif11157 A hardness measurement test was conducted using the pencil. For hardness of 11H or more, the correlation data between the pencil hardness test and the abrasion resistance test shown in Figure 1 was used to estimate the hardness as equivalent to 11H, 12H, or 13H. *For polishing with a diamond whetstone, a #5000 whetstone was used and polished with a hand polisher for about a minute while running water. *Each test was carried out five times to check for peeling or scratches. *A 10cm x 10cm glass plate was used as the sample.

[0025] From the above test results, it was found that under comfortable humidity conditions (65% to 75%), if the film thickness is about 20 μm, it has a hardness of 12H or more, and can be post-processed (polished with a diamond grinding wheel) without peeling or scratches.

[0026] Table 4 below shows the abrasion resistance and gloss retention of the coating film at different pencil hardnesses for the coating agent of sample 12 in Table 3 above. These results show that a coating layer hardness of about 12H provides 10 to 20 times more abrasion resistance and excellent gloss compared to the marble of samples 1 and 2. [Table 4] Test Method *Hardness was measured using the JIS K5600 pencil hardness test, and the film thickness on the glass plate was 20 μm. *The JIS K5600 pencil hardness test standard is up to 6H, but in reality, there are pencils up to 10H equivalent, so the hardness was measured using those pencils. For 11H equivalent or higher, the pencil hardness test shown in Figure 1 was used to estimate 11H equivalent or 12H equivalent based on the correlation data of the abrasion resistance test. *Abrasion resistance tests were performed according to JIS H8503-1989. *GC#100 was used as the abrasive. *The initial gloss value of both the marble and the coating layer was set to 80 during the test. *One hour of wear resistance testing is equivalent to approximately one year in actual operation.

[0027] From the above results, when the hardness of the coating layer is equivalent to 12H or more, the wear resistance and gloss retention are significantly improved, and a maintenance-free coating can be formed. As a result, it can be confirmed that the wear resistance and gloss retention are 10 to 20 times higher than that of normal marble. In addition, it was confirmed that under comfortable humidity conditions (65 to 75%), when the amount of colloidal silica in the aqueous solvent exceeds 15 wt% of the total amount of colloidal silica 100 wt%, the hardening of the coating film is extremely reduced, and peeling and polishing scratches occur during polishing. However, in the results shown in Table 3 above, when the amount of colloidal silica in the aqueous solvent is less than 5 wt% of the total amount of colloidal silica 100 wt% out of the 20 to 40 wt% colloidal silica, cracks occur over time. Therefore, it can be understood that under comfortable humidity conditions (65-75%), by containing 5-15 wt% water-solvent colloidal silica relative to the total amount of colloidal silica (100 wt%), rapid hardening is prevented and peeling is unlikely to occur even when post-polished.

[0028] From the above results, it can be seen that by making the hardness of the coating layer equivalent to 12H or more, it is possible to achieve a mirror finish without peeling during post-treatment (polishing with a diamond grinding wheel), and the film has a gloss retention that is 10 to 20 times longer than that of normal marble polishing, making it possible to provide a maintenance-free type of stone material.

[0029] First, the total amount of silane, including polyorganosiloxane and silane coupling agent, was fixed at 40%, and the catalyst was 6 to 10 wt% phosphoric acid catalyst and 35 wt% colloidal silica. Samples No. 1 to 15 were prepared by varying the amount of colloidal silica in water solvent by 0 to 20 wt% relative to the total colloidal silica of 100 wt%.

[0030] [Table 5]

[0031] Each sample based on Table 5 above was applied to marble (Bianco Carrara) under the following comfortable humidity conditions (65-75% - Table 6), high humidity conditions (75% or more - Table 7), and low humidity conditions (65% or less - Table 8). The results of checking the finish (whether there is cracking or peeling), adhesion, hardness, etc. are shown below. Comparative Experiment 1

[0032] [Table 6] The coating film was evaluated by the following methods. *The comfortable humidity conditions for coating were set in the autumn when the weather was fine, with the humidity gauge measuring 65-75%. *Finish check: Visually check for cracks or peeling. *Adhesion test method: According to the cross-cut method described in JIS K5400, 100 cross-cuts of 1 mm2 were cut into 1 cm2 of the coating surface of the test piece, cellophane tape was pressed onto the cross-cuts and then peeled off, and the adhesion was judged based on the number of remaining cross-cuts out of the 100. *Pencil hardness test: conforms to JIS K-5600. The test piece is fixed on a horizontal table with the coating surface facing up, and the pencil is held at an angle of about 45 degrees. The tester scratches the coating by pressing the pencil about 1 cm in front of the tester at a uniform speed while pressing the coating surface as hard as possible without breaking the lead. The hardness symbol of the hardest pencil that does not break the coating surface is shown. However, although the JIS pencil hardness test standard goes up to 6H, actual pencils go up to 10H, so the test was conducted at that pencil hardness. For 11H and above, 11H, 12H, and 13H were estimated based on the correlation data of the pencil hardness test and the abrasion resistance test in Figure 1.

[0033] From the above results, under comfortable humidity conditions (65-75%), good results were obtained for all samples except 5, 6, 10, 11, and 15. For 6 and 11, the absence of aqueous colloidal silica and the large amount of phosphoric acid catalyst accelerated the hardening extremely, which caused the coating to shrink strongly and fine cracks to occur. On the other hand, for 5, 10, and 15, although the amount of phosphoric acid catalyst was large like 6 and 11, the amount of aqueous colloidal silica was also large, which is thought to be why the hardening of the coating was delayed, the hardness was low, and peeling occurred in the adhesion test. From these results, it was found that an excessive amount of phosphoric acid catalyst under comfortable humidity conditions can cause cracks, but by including 5-15 wt% aqueous colloidal silica, the hardening is balanced, and even if the amount of phosphoric acid catalyst is large, cracks and peeling in the adhesion test are not observed. Comparative Experiment 2

[0034] [Table 7] The coating film was evaluated by the following methods. *The high humidity conditions for coating were performed during the rainy season with a humidity meter reading of 75% or higher. *Finish check: Visually check for cracks or peeling. *Adhesion test method: According to the cross-cut method described in JIS K5400, 100 cross-cuts of 1 mm2 were cut into 1 cm2 of the coating surface of the test piece, cellophane tape was pressed onto the cross-cuts and then peeled off, and the adhesion was judged based on the number of remaining cross-cuts out of the 100. *Pencil hardness test: conforms to JIS K-5600. The test piece is fixed on a horizontal table with the coating surface facing up, and the pencil is held at an angle of about 45 degrees. The tester scratches the coating by pressing the pencil about 1 cm in front of the tester at a uniform speed while pressing the coating surface as hard as possible without breaking the lead. The hardness symbol of the hardest pencil that does not break the coating surface is shown. However, although the JIS pencil hardness test standard goes up to 6H, actual pencils go up to 10H, so the test was conducted at that pencil hardness. For 11H and above, 11H, 12H, and 13H were estimated based on the correlation data of the pencil hardness test and the abrasion resistance test in Figure 1.

[0035] As can be seen from Table 7, under high humidity conditions (humidity 75% or higher), the less water-solvent colloidal silica there is, the more curing proceeds, and the more phosphoric acid catalyst there is, the more curing proceeds. However, even if the amount of phosphoric acid catalyst was high, as in sample 15, peeling occurred in the adhesion test when the amount of water-solvent colloidal silica was high. This is similar to the results in comfortable humidity conditions in Table 6, and is thought to be because even if there was a lot of phosphoric acid catalyst, the amount of water-solvent colloidal silica was high, slowing down curing, and under high humidity conditions curing was even slower. It is also clear that samples 1, 6, and 11 had good curing conditions under high humidity conditions, with no cracks occurring. From these findings, under high humidity conditions, the appropriate amount of water-solvent colloidal silica is 0-15wt%, and the appropriate amount of phosphoric acid catalyst is more than 5wt% but not more than 10wt% by weight. Comparative Experiment 3

[0036] [Table 8] The coating film was evaluated by the following methods. *The comfortable humidity conditions for coating were set at 65% or less on a fine autumn day using a hygrometer. *Finish check: Visually check for cracks or peeling. *Adhesion test method: According to the cross-cut method described in JIS K5400, 100 cross-cuts of 1 mm2 were cut into 1 cm2 of the coating surface of the test piece, cellophane tape was pressed onto the cross-cuts and then peeled off, and the adhesion was judged based on the number of remaining cross-cuts out of the 100. *Pencil hardness test: conforms to JIS K-5600. The test piece is fixed on a horizontal table with the coating surface facing up, and the pencil is held at an angle of about 45 degrees. The tester scratches the coating by pressing the pencil about 1 cm in front of the tester at a uniform speed while pressing the coating surface as hard as possible without breaking the lead. The hardness symbol of the hardest pencil that does not break the coating surface is shown. However, although the JIS pencil hardness test standard goes up to 6H, actual pencils go up to 10H, so the test was conducted at that pencil hardness. For 11H and above, 11H, 12H, and 13H were estimated based on the correlation data of the pencil hardness test and the abrasion resistance test in Figure 1.

[0037] Under low humidity conditions (humidity 65% ​​or less), good results were obtained for all samples except for 1, 5, 6, 10, 11, and 15. As with the results in Table 6 under comfortable humidity conditions, 1, 6, and 11 tend to have a tendency to accelerate curing due to the large amount of phosphoric acid catalyst. Under low humidity conditions, the coating cures faster in samples 1, 6, and 11, which do not contain water, and it is thought that this causes more shrinkage and fine cracks to occur. As a result, many peelings also occurred. On the other hand, although 5, 10, and 15 have a large amount of phosphoric acid catalyst, they also contain a large amount of water-solvent colloidal silica, so it is thought that the cure of the coating is delayed even under low humidity conditions, the hardness is low, and peeling occurred in the adhesion test. From these results, when the water-solvent colloidal silica is 0 wt% under low humidity conditions, the shrinkage due to curing is strong, causing cracks and many peelings. It was found that even under low humidity conditions, the hardening properties were balanced by including 5 to 15 wt% water-solvent colloidal silica for a total of 100 wt% colloidal silica, and that no cracks or peeling in adhesion tests were observed even when the amount of phosphoric acid-based catalyst was increased.

[0038] As shown in Table 7, under high humidity conditions, stable curing was obtained at a weight ratio of more than 5 wt% to 10 wt% phosphoric acid catalyst and 0-15 wt% water-solvent colloidal silica, but under comfortable humidity conditions (humidity 65-75%) and low humidity conditions (humidity 65% ​​or less), cracks occurred when the water-solvent colloidal silica was 0 wt%, as shown in Tables 6 and 8, and peeling also occurred in the adhesion test. From these results, it can be seen that the appropriate amounts for stable curing promotion under each temperature and humidity condition are a weight ratio of more than 5 wt% to 10 wt% phosphoric acid catalyst and 5-15 wt% water-solvent colloidal silica. Effect of the invention

[0039] The present invention can provide a maintenance-free vitreous inorganic coating agent for stone tiles that stably accelerates curing under a wide range of humidity conditions, including the above-mentioned low humidity (65% or less), comfortable humidity (65 to 75%), and high humidity (75% or more), and a method for manufacturing such tiles. [Brief description of the drawings]

[0040] [Figure 1] Figure 1 shows the correlation data between the pencil hardness test and the abrasion resistance test.

Claims

1. The present invention relates to a method for producing a silica-based composition comprising: a polyorganosiloxane, at least one of which is a mixture of alkoxysilanes having tetrafunctional and trifunctional groups; a silane coupling agent having an epoxy functional group; and an organic solvent-dispersed ultrafine colloidal silica having an average particle size of 5-60 nm and a silica solids concentration of 40 wt %. The composition is 30-60 wt % of the polyorganosiloxane, 5-20 wt % of the silane coupling agent, and 100 wt % of the ultrafine colloidal silica. %. The maintenance-free inorganic glass coating agent for stone tiles contains 20 to 40 wt % ultrafine colloidal silica, and in order to enhance the reaction curing property, a phosphoric acid catalyst is added in a weight ratio of more than 5 wt % to 10 wt % without using a titanium-based catalyst and / or an aluminum-based catalyst, and among the 20 to 40 wt % ultrafine colloidal silica, 5 wt % to 15 wt % of water-solvent colloidal silica having a silica solids concentration of 20 wt % is added relative to the total amount of the ultrafine colloidal silica.

2. The present invention relates to a method for producing a silica-based composition comprising: a polyorganosiloxane, at least one of which is a mixture of alkoxysilanes having tetrafunctional and trifunctional groups; a silane coupling agent having an epoxy functional group; and an organic solvent-dispersed type ultrafine colloidal silica having an average particle size of 5 to 60 nm and a silica solids concentration of 40 wt %, per 100 weight ratio of a main component. The polyorganosiloxane is 30 to 60 wt %, the silane coupling agent is 5 to 20 wt %, the ultrafine colloidal silica is 20 to 40 wt % as a whole, and a titanium-based catalyst and / or an aluminum-based catalyst are not used as a catalyst for enhancing reaction curing property, and a phosphoric acid-based catalyst is added in a weight ratio of more than 5 wt % and not more than 10 wt %, and among the ultrafine colloidal silica of 20 to 40 wt %, a water-solvent colloidal silica having a silica solids concentration of 20 wt % is added in an amount of 5 wt % based on the total amount of the ultrafine colloidal silica. % to 15 wt % of a vitreous inorganic coating agent for maintenance-free stone tiles, the method comprising the steps of: adjusting the viscosity of the vitreous inorganic coating agent for maintenance-free stone tiles to 3 cSt to 6 cSt (mm2 / s), coating the agent on a stone floor surface whose stone surface has been roughened in advance by diamond polishing; curing the agent at room temperature 1 hour to 1 day after the coating process to a pencil hardness equivalent to or greater than 12H when measured based on correlation data between a pencil hardness test and an abrasion resistance test; and then polishing the surface of the coating layer with a diamond grindstone to obtain a surface roughness of Rmax 0.8s or less and a specular gloss of 80 or more.

Citation Information

Patent Citations

  • Coating composition

    JP1988128082A

  • Antistatic mat for synthetic resin floorboard material

    JP2003184292A

  • Photocatalytic coating composition

    JP2005023270A

  • Substrate with self-cleaning coating

    JP2005528313A

  • Ordinary temperature-curable inorganic coating film and coating agent

    JP2006307124A